2020
DOI: 10.21203/rs.3.rs-38024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No Difference in Physical Activity Associated with Cannabis Use Status in a Nationally Representative Sample of U.S. Adults

Abstract: Background: Prior research examining the relationship between cannabis use, sedentary behavior, and physical activity has generated conflicting findings, potentially due to biases in the self-reported measures used to assess physical activity. This study aimed to more precisely explore the relationship between cannabis use and sedentary behavior/physical activity using objective measures. Methods: Data were obtained from the 2005-2006 National Health and Nutrition Examination Survey. 2,092 participants (ages 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Two studies included in this review employed self-reported measures of physical activity levels, finding no significant differences between cannabis users and non-users, consistent with Ong et al's ( 2020 ) analysis of accelerometer detected physical activity, which determined no difference in light or moderate/vigorous physical activity between 249 cannabis users and 1843 non-users. Contrastingly, several longitudinal studies found significantly more cannabis users meeting WHO guidelines for physical activity than non-users (Korn et al 2018 ; Ngueta et al 2015 ; Rajavashisth et al 2012 ).…”
Section: Discussionsupporting
confidence: 77%
“…Two studies included in this review employed self-reported measures of physical activity levels, finding no significant differences between cannabis users and non-users, consistent with Ong et al's ( 2020 ) analysis of accelerometer detected physical activity, which determined no difference in light or moderate/vigorous physical activity between 249 cannabis users and 1843 non-users. Contrastingly, several longitudinal studies found significantly more cannabis users meeting WHO guidelines for physical activity than non-users (Korn et al 2018 ; Ngueta et al 2015 ; Rajavashisth et al 2012 ).…”
Section: Discussionsupporting
confidence: 77%